Growth of green deli water apple (Syzygium samarangense (Blume) Merr. & Perry) on Difference Plant Materials and IBA Concentrations - nervi farida sinaga; Ferry Ezra Sitepu (Universitas Sumatera Utara, 2016)
The objectives of this research was to study the growth of green deli water apple (Syzygium samarangense (Blume) Merr. & Perry on difference plant materials and IBA concentrations. This research was conducted at experimental field of Agriculture Faculty, University of North Sumatera, Medan on August until October 2015, using randomized block design with two factors, i.e cutting plant materials (branches with shoot and branches without shoot) and IBA concentration (0; 50; 100; and 150 ppm) with 3 replications. The result showed that the growth of green deli water apple with branches without shoot better than branches with shoot, the application of 100 ppm IBA concentration has given better effect than the other treatments for growth of green deli water apple and the best combination for growth of green deli water apple was branches without shoot and 100 ppm IBA concentration.